Effects of footwear cushioning on leg and longitudinal arch stiffness during running - Holowka, N. B.; Gillinov, S. M.; Virot, E.; Lieberman, D. E. (Journal of Biomechanics, 2022)
During running, humans increase leg stiffness on more compliant surfaces through an in-series spring relationship to maintain constant support mechanics. Following this notion, the compliant midsole material of standard footwear may cause individuals to increase leg stiffness while running, especially in footwear with very thick midsoles. Recently, researchers have also proposed that footwear stiffness can affect the stiffness of the foot`s longitudinal arch (LA) via a similar mechanism. To test these ideas, we used 3D motion capture to record 20 participants running on a forceplate-instrumented treadmill while barefoot, and while wearing three types of sandals composed of materials ranging an order of magnitude in Young`s modulus: ethylene vinyl acetate (EVA), and two varieties of polyurethane rubber (R30 and R60). We calculated leg stiffness using standard methods, and measured LA stiffness based on medial midfoot kinematics. While there was an overall significant effect of footwear on leg stiffness (P = 0.047), post-hoc tests revealed no significant differences among individual pairs of conditions, and there was no effect of footwear on LA stiffness. However, participants exhibited significantly greater LA compression when barefoot than when running in EVA (P = 0.004) or R30 (P = 0.036) sandals. These results indicate that standard footwear midsole materials are too stiff to appreciably affect leg stiffness during running, meaning that increasing midsole thickness is unlikely to cause individuals to alter their leg stiffness. However, use of footwear does cause individuals to restrict LA compression when compared to running barefoot, and further research is needed to understand why.